Traditional Fermentation and Distillation of Raffia Palm Sap for the Production of Bioethanol in Bayelsa State, Nigeria - Ohimain, Elijah I.; Tuwon, Patrick E.; Ayibaebi, Ekiemene A. (Journal of Technology Innovations in Renewable Energy, 2013)
The production of alcoholic beverages from the sap of raffia palm, Raphia hookeri, has continued for decades in West Africa, but the detailed processes had never been documented before. The objective of this study is to document the traditional process of ethanol production, with the aim of scaling up the process for the production of fuel ethanol. Ten smallholder ethanol production facilities were randomly selected, and triplicate samples of the process intermediates were collected and analysed, including fermented palm sap, first and second distillate, first and second stillage. Results show that the percentage of ethanol was significantly different (P<0.05) among the different intermediates. The highest ethanol presence was recorded in the second distillate (39-61.5%), followed by the first distillate (18.83-39%), then the first stillage (5.80-10.20%), the palm sap (10.50-15.30%) and finally the second stillage (3.40-5.80%).Yeast population, pH, sugar, specific gravity and electrical conductivity differed significantly among the various sites and intermediates. Wood (105-155kg) was used as fuel to boil 280-480L of fermented palm sap producing 20L of 39-61.5% ethanol. The smallholder processors are however challenged by the poor distillation apparatus and the lack of ethanol dehydration facilities. The study concludes by recommending the modification of the Nigerian Biofuel Policy (2007) to allow the use of hydrous ethanol in automobiles and low concentration ethanol for household cooking.